PENGARUH GAYA KEPEMIMPINAN, KOMPETENSI, DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI - Novianti, Dewi; Astuti, Nelly; Tri Setyo Mulyani, Hendarti (Jurnal Progresif Manajemen Bisnis, 2021)
The theories used in this research are HRM theory, Leadership Style theory, Competence theory, Communication theory and Performance theory. The method used in this research is to use a quantitative approach through a sample approach. Probability Sampling, is a sampling technique that provides equal opportunities for each element (member) of the population to be selected as a member of the sample. Through the Snowball Sampling approach, it is a technique of determining the sample which is initially small in number, then increases. It's like a rolling snowball that grows bigger over time. The sample in this study were employees of the Food and Agriculture Office of Pangkal Pinang, which amounted to 100 people. The results of this study indicate that the Adjusted R2 is 0.482 or equivalent to 48.2%. It can be concluded that the independent variables (leadership style, competence, and communication) can explain and influence the dependent variable of employee performance by 48.2%. The remaining 51.8% can be explained by other variables not used in this study. The first hypothesis of H1 does not show a positive and significant t value. This means that the t-test obtained individually (partial) for the leadership style variable has no positive and significant effect on employee performance at the Food and Agriculture Office of Pangkal Pinang City. H0 is accepted with a value of 0.800. The second hypothesis of H2 can show a positive and significant t value. This means that it is stated that individually (partial) competence has a positive, and significant effect on employee performance at the Food and Agriculture Office of Pangkal Pinang City. H2 can be accepted with a value of: 2.273. The third hypothesis of H3 can show a positive and significant t-value result. This means that it is stated that individually (partial) communication has a positive and significant effect on employee performance at the Food and Agriculture Office of Pangkal Pinang City. H3 can be accepted with a value of 3,703. The fourth hypothesis from the F test states that the value obtained by the leadership style of competence and communication has a positive, and significant effect on employee performance at the Food and Agriculture Office of Pangkal Pinang City. H4 is accepted with a value of: 31.751.